NECESIDAD DE TIPIFICAR COMO DELITOS AUTÓNOMOS EN EL CÓDIGO ORGÁNICO INTEGRAL PENAL (COIP) EL CIBERACOSO Y LA EXTORSIÓN A TRAVÉS DE LOS MEDIOS ELECTRÓNICOS POR CONSTITUIR GRAVES AFECTACIONES A LOS DERECHOS DE LOS CIUDADANOS - RODAS MELGAR, JACKSON PATRICIO (2016)
This research work it could develop according to the existing problems concerning the need to establish as separate offenses in the Code of Integral Criminal (COIP) cyberbullying and extortion by being serious effects on the rights of citizens, it is a problem that is growing considerably in our society. To strengthen this research work I have considered as a general objective to carry out a theoretical legal study of the need to establish as prejudicial to the rights of integrity such as cyber bullying and extortion through electronic media behavior, which was checked through the application of methods and techniques of scientific, which led me to achieve results, allowing that the proposal for reform and typing of law. A more conceptual , doctrinal , legal and bibliographic collection, thirty surveys were conducted to people who know the subject of investigation, five interviews with legal professionals in our city, with the data I could gather , it was concluded that respondents as respondents if they believe it is appropriate that is reformed and is punishable as separate crimes cyberbullying and extortion , they also told us that the competent authorities should take appropriate action to mitigate this type of crime . 5 Field research showed that it should establish and amend the Code of Integral Criminal (COIP), to ensure an intimate, comprehensive and violence-free life of people in all areas, as stated in our Constitution Republic of Ecuador. Comparative Law allowed me to establish the multiple incidents and consequences now been presented as a result of two major problems that every day they grow and are causing serious and irreparable damage to the inner life of people, as they are cyberbullying and extortion through electronic media.